Pemanfaatan Fasilitas Kredit Usaha Rakyat (KUR) Terhadap Peningkatan Usaha Mikro Kecil Dan Menengah (UMKM) (Studi Kasus Bank Mandiri Kantor Kas Manado Paal Dua) - Mokalu, Olivia Johana; Montolalu, John; Keles, Dantje (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
The aim of this research to know how big the influence of giving KUR concern to raising effort little micro and medium in Manado city. Citizenry effort credit is working capital finance to productive and viable business debtors but not having additional collateral or additional collateral is sufficient. Form of research using on this research is correlational research with quantitative analysis. This research doing in Mandiri Bank in Paal 2, with population 102 customer and 51 sample costumer. Analysis technique using in this research is simple regression analysis. The result in this research show the strong relationship between giving KUR with increase UMKM seeing from the result and from the result determination coefficient that means the relation between Mandiri Bank is determine by giving KUR through regression similarity. Remnant determined by another factor. The summary of this research have an effect to increase UMKM. The verification doing with T-test with Tarithmetic to X (KUR) and Ttable in significant that means comparison between Tarithmetic and Ttable is tarithmetic more than ttable. Suggestion from research are other people that giving KUR as Mandiri Bank to help agent of business to increase the business and its better for business agent to get more information that can advance their business.Â Keyword: Citizenry Effort Credit (KUR), Little and Medium Micro Effort (UMKM)